Dispute Resolution Analysis Against Copyright Infringement in The Song "Halo-Halo Bandung" Which Was Plagiarism in Malaysia "Hello Kuala Lumpur" - Fansiska, Claudya; Mawaddah, Dzulfah; Diniarti, Laura Safira (Golden Ratio of Data in Summary, 2025)
This study analyzes the copyright dispute between the song Halo-Halo Bandung, created by Ismail Marzuki, and the song Hello Kuala Lumpur, uploaded by a YouTube account from Malaysia. This study aims to identify the background of the dispute and analyze its resolution based on the Copyright Act and international standards. The research method used is normative law with a case study approach. The song's authenticity is assessed through a comparative analysis of the melody, lyrics, and musical structure, and is supported by a plagiarism detection tool. The study results indicate that Hello Kuala Lumpur has substantial similarities with Halo-Halo Bandung, so it is suspected of violating copyright. The dispute can be resolved through negotiation (Alternative Dispute Resolution), arbitration, or civil lawsuits in the Commercial Court. From an international law perspective, this case highlights the role of the Berne Convention and WIPO in resolving cross-border copyright disputes. The potential legal impacts of this case include a precedent for protecting works of art at the ASEAN level and strengthening copyright regulations in Indonesia. The solutions offered include stopping the distribution of plagiarized songs, compensating the original creators, and increasing awareness and compliance with copyright in the future.